A history of previous childbirths is linked to women's white matter brain age in midlife and older age. Issue 13 (12th June 2021) - Voldsbekk, Irene; Barth, Claudia; Maximov, Ivan I.; Kaufmann, Tobias; Beck, Dani; Richard, Genevieve; Moberget, Torgeir; Westlye, Lars T.; de Lange, Ann‐Marie G.
Abstract: Maternal brain adaptations occur in response to pregnancy, but little is known about how parity impacts white matter and white matter ageing trajectories later in life. Utilising global and regional brain age prediction based on multi‐shell diffusion‐weighted imaging data, we investigated the association between previous childbirths and white matter brain age in 8, 895 women in the UK Biobank cohort (age range = 54–81 years). The results showed that number of previous childbirths was negatively associated with white matter brain age, potentially indicating a protective effect of parity on white matter later in life. Both global white matter and grey matter brain age estimates showed unique contributions to the association with previous childbirths, suggesting partly independent processes. Corpus callosum contributed uniquely to the global white matter association with previous childbirths, and showed a stronger relationship relative to several other tracts. While our findings demonstrate a link between reproductive history and brain white matter characteristics later in life, longitudinal studies are required to establish causality and determine how parity may influence women's white matter trajectories across the lifespan. Abstract : Utilising global and regional brain age prediction based on multi‐shell diffusion‐weighted imaging data, we investigated the association between previous childbirths and white matter brain age in 8, 895 women in the UK Biobank cohort (age range = 54–81 years). The results showed that number of previous childbirths was negatively associated with white matter brain age, potentially indicating a protective effect of parity on white matter later in life. Corpus callosum contributed uniquely to this association, and showed a stronger relationship relative to several other tracts.